Reinventing the Wheel-Molecular Plating as a Method for the Production of Rotating Targets - Greene John; Mohs Connor; Mueller-Gatermann Claus; Knaack Russell (EPJ Web of Conferences)
The technique of molecular plating for the deposition of target layers has become relatively mature in recent years and is the method of choice for the development of actinide targets starting from solution. At the Center for Accelerator Target Science (CATS) this technique has been employed for the preparation of small target wheels deployed within the large gamma-ray arrays Gammasphere and GRETINA. Experiments using the Argonne Gas-Filled Analyzer (AGFA) for heavy-element spectroscopy and requiring high-intensity beams have spurred the development of larger diameter rotating targets to be used for these studies. In the past these large target wheels have been fashioned mostly from stable isotopic metals, but newer experimental demands have moved towards employing actinide as well as stable lanthanide targets. Based on existing set-ups and experience with smaller target wheel production, new molecular plating cells for preparing the target sectors needed for both the AGFA target wheel as well as the previously deployed large rotating wheel used in the heavy-element target chamber and for the N=126 Experiment have been designed and commissioned. Current work on the production of these targets and some early results are presented.